Penerapan Terapi Genggam Jari Dan Nafas Dalam Untuk Mengetahui Perubahan Tekanan Darah Pada Lansia Penderita Hipertensi - Karunia Rosa; Erika Dewi Noorratri; Panggah Widodo (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2023)
Introduction : Aging is a biological process that cannot be avoided, the aging process occurs naturally. This can cause physical, mental, social, economic and psychological problems. Hypertension is a disease caused by systolic blood pressure above 140 mmHg and diastolic blood pressure above 90 mmHg. Finger grip relaxation technique is a relaxation technique that is very simple and easy to do by anyone related to the fingers and the flow of energy in our bodies. Finger grip relaxation can relieve tension and stress, so it can reduce pain and holding your fingers while taking deep breaths can reduce emotional tension Objectives : To describe the results of blood pressure before finger gripping therapy and deep breathing, to describe blood pressure results after finger gripping and deep breathing, to describe the development of blood pressure before and after finger holding and deep breathing in 2 respondents, to describe the comparison of the final results between 2 respondents. Method : Pre-experimental with one group pretest-post test design. The number of subjects studied amounted to 2 respondents. Result : There was a decrease in blood pressure after holding finger therapy and deep breathing for 3 days. Conclution : Finger gripping therapy and deep breathing have an effect on reducing blood pressure in elderly hypertensives.